Hand grip strength in the adult Malaysian population - Kamarul, Tunku; Ahmad, T.S.; Loh, W.Y. (Hong Kong University Press / Hong Kong Academy of Medicine Press, 2006)
PURPOSE: To measure the hand grip strength of Malaysians aged 18 to 65 years.